Nursing outcome “Severity of infection”: conceptual definitions for indicators related to respiratory problems - Rodríguez Acelas, Alba Luz; Reich, Rejane; de Abreu Almeida, Miriam; Oliveira Crossetti, Maria da Graça; de Fátima Lucena, Amália (Investigación y Educación en Enfermería, 2016)
Objective. Build conceptual definitions for some indicators of the nursing outcome Infection Severity in the Nursing Outcomes Classification (NOC) related to respiratory problems, based on scientific evidence of signs and symptoms of infection in adults. Methods. Integrative literature review with search in the databases PubMed, CINAHL, LILACS and SCOPUS. Studies whose full texts were available, published in Spanish, Portuguese or English, using the descriptors infection severity, nursing outcomes classification NOC, respiratory infections and respiratory signs and symptoms. Results. Nine publications were analyzed that supported the elaboration of the conceptual definitions for eight indicators of the Nursing Outcome Infection Severity: purulent drainage, fever, chilling, unstable temperature, pain, colonization of drainage cultivation, white blood cell count elevation and white blood cell count drop. Conclusion. This study contributed to understand the terms used in the nursing outcome Infection Severity, in order to improve and facilitate the use of the NOC, as it enhances the conceptual clarity of the selected indicators with a view to producing better scientific evidence. How to cite this article: Rodríguez-Acelas AL, Reich R, Almeida MA, Crossetti MGO, Lucena AF. Nursing outcome “Infection Severity”: conceptual definitions for indicators related to respiratory problems. Invest Educ Enferm. 2016; 34(1): 38-45